SAT0193 Results of a randomized placebo controlled phase ia study of AGS-009, a humanized anti-interferon-α monoclonal antibody in subjects with systemic lupus erythematosus. (23rd January 2014) - Tcherepanova, I.; Curtis, M.; Sale, M.; Miesowicz, F.; Nicolette, C.
Abstract : Background: Unabated Type I interferon expression is implicated in the pathogenesis of systemic lupus erythematosus (SLE). A monoclonal anti-IFN-α antibody, AGS-009, which neutralizes a broad range of IFN-α subtypes was developed and humanized for use as a therapeutic treatment for SLE. This is the first human clinical trial using this antibody. Objectives: To evaluate safety, pharmacokinetics (PK) and IFN-α neutralizing capacity of a single intravenous (i.v) infusion of AGS-009 in adults with mild to moderate SLE. IFN-a neutralization was assessed by monitoring IFN-α-inducible gene transcription levels. Methods: We conducted a phase Ia multicenter, randomized, double blind, placebo-controlled single dose escalation study. Subjects included in the study had mild to moderate SLE based on their disease activity index and clinical laboratory test results but were not screened for elevated IFN-a activity at baseline. Subjects were randomized in 3:1 ratio within each cohort to receive a single i.v. infusion of AGS-009 at 0.01, 0.1, 0.6, 3, 10 and 30 mg/kg or placebo. There were 25 subjects in total (4 subjects per dose level with one replacement subject) and all subjects received AGS-009 or placebo in combination with standard of care. Subjects were monitored for safety based on adverse events (AEs), physical exam and clinical laboratory tests. Serum samples were collected longitudinally before and after drug administration for a period of 85 days to evaluate pharmacokinetics (PK) using a validated ELISA assay. Longitudinal whole blood samples were collected before and after treatment as well and changes in expression levels of 27 IFN-α-inducible genes (IFN-α signature) were evaluated by RT-PCR in five cohorts ≥0.1 mg/kg dose level. Results: AGS-009 was safe and well tolerated at each dose level with no AGS-009-related SAEs or dose-limiting toxicities observed. Pharmacokinetic analysis showed that peak serum concentration of AGS-009 increased proportionally to the dose administered ranging from 1.59×10 2 -6.82×10 5 ng/mL. Mean terminal half-life ranged from 270 to 489 hours across the dosing groups and was consistent with prior results obtained in non-human primates. Prior to AGS-009 treatment, the IFN-α-inducible gene signature was elevated in 17 of 21 subjects evaluated, compared to an average across 8 healthy individuals. At AGS-009 dose levels above 0.6 mg/kg, subjects with elevated baseline IFN-a signatures demonstrated marked decreases in median expression levels which was not observed in placebo subjects. The degree of reduction in post-treatment IFN-α gene expression suggests a trend with the dose level administered. IFN-a signatures in the 4 subjects without elevated levels at baseline were not modulated. Conclusions: AGS-009 was shown to be safe and well tolerated at all dose levels. Peak blood levels of AGS-009 following a single i.v. dose were proportional to the doses administered and the half-life remained relatively constant at 11-20 days across the dose groups. AGS-009 treatment at doses >0.6 mg/kg resulted in significant neutralization of IFN-a signatures, consistent with the proposed mechanism of action. Cumulative data from this study warrants continuation of clinical development of AGS-009 and establishing inclusion criteria based on elevated baseline IFN-a levels. Disclosure of Interest: I. Tcherepanova Employee of: Argos Therapeutics, M. Curtis Employee of: Argos Therapeutics, M. Sale Consultant for: Argos Therapeutics, F. Miesowicz Shareholder of: Argos Therapeutics, Employee of: Argos Therapeutics, C. Nicolette Shareholder of: Argos Therapeutics, Employee of: Argos Therapeutics